The influence of dissolved organic carbon and ultraviolet radiation on the genomic integrity of Daphnia magna. (15th September 2016) - Wolf, Raoul; Andersen, Tom; Hessen, Dag O.; Hylland, Ketil
Summary: Many northern freshwaters are currently experiencing a pronounced 'browning', that is an increase in terrestrially derived dissolved organic carbon (DOC). Chromophoric DOC offers protection against photodamage by absorbing harmful ultraviolet radiation (UVR), but may also produce free radicals and reactive oxygen species (ROS) following photoactivation. The aim of this study was to explore the combined effects of DOC and UVR on DNA integrity of limnetic zooplankton. Specifically, DNA strand breaks in the cladoceran Daphnia magna were investigated. DNA strand breaks were assessed using comet assays with treatment of individual daphnids. A four‐by‐four design was used for exposure to DOC (2·03, 5, 10 and 20 mg L −1 ), UVA (0, 10·8, 21·7 and 43·4 μmol m −2  s −1 at 390 nm) and their combinations. ROS production from photoactivated DOC was quantified using a modified DCFH‐DA in vitro ROS detection assay. While UVA had no effects on DNA damage above background levels (4·5–2·8%), we observed increased DNA damage in DOC treatments (4·1–9·1%). The highest increase was observed in combined DOC and UVA treatments (up to 20·2%). ROS production showed similar patterns, as simultaneous exposure to both DOC and UVA resulted in higher formation rates than exposure to DOC and UVA alone (up to 684·5 μmol L −1 vs. 5·9 to 13·1 and 27·5 to 83·9 μmol L −1, respectively). This indicates that the observed increase in DNA damage was due to ROS production of photoactivated DOC. This study showed that strong interactive effects of short‐wave radiation and DOC could have major genomic impacts on pelagic biota. With future scenarios of increased DOC, our study points towards increasing oxidative stress for ecosystems. These findings highlight an important aspect of climate change at the intersection between ecology, limnology and toxicology. A lay summary is available for this article. Abstract : Lay Summary